Book Review: Creswell, John. (1997). Qualitative inquiry and research design: Choosing among five traditions. - Catherine Compton Lilly (Networks: An Online Journal for Teacher Research, 1998)
As a teacher who has experimented with classroom research, I know that "doing research" can seem overwhelming. If you're like me, you took a research methodology course back in college which focused on deciphering quantitative studies and learning seemingly endless lists of terms like validity, sample, and verification. Now you may be involved in a teacher research group affiliated with a local college that meets monthly to discuss how people's research projects are progressing. However, that doesn't seem to be adequate to equip you for the research task. A book that I find particularly helpful is Qualitative Inquiry and Research Design: Choosing Among Five Traditions by John Creswell. Although this book is not written specifically for teacher-researchers or even educators, both novice and experienced teacher-researchers will find this book useful. In his book, Creswell has identified five traditions of qualitative research which he compares and contrasts throughout the book. The book is full of engaging examples and specific suggestions tailored to each of the five research traditions.